Tertiary Lymphoid Organs in Cancer Immunology: Mechanisms and the New Strategy for Immunotherapy - Lin, Liangbin; Hu, Xiang; Zhang, Huiyuan; Hu, Hongbo (Frontiers in Immunology, 2019)
The immune system plays pivotal roles in the occurrence and progression of cancers. As blockage of immune-checkpoint has been proven effective at improving anti-tumor immune response in multiple tumor types, the tumor immunotherapy still faces many challenges. Emerging evidence indicates lymphoid organ-like structures, also called tertiary lymphoid organs (TLOs) or ectopic lymphoid organs (ETOs), have been identified in cancers, as the result of lymphoid neoorganogenesis. The prognostic value of TLOs in cancer patients has been evaluated with debates, however, such well-organized lymphoid structures in the site of cancer indicate TLOs are the important modulators of cancer immunological microenvironment. TLOs have attracted remarkable efforts to investigate their neoorganogenesis and function in immune responses, aiming to develop new strategies for cancer immunotherapy. In this review, we summarize the current understandings about the molecular and cellular mechanisms governing the formation and function of TLOs in immune responses against cancer.